2009
DOI: 10.1108/17410380910997254
|View full text |Cite
|
Sign up to set email alerts
|

A methodology for cost‐oriented assembly line balancing problems

Abstract: Purpose -The efficiency of assembly lines is a critical factor for the competitiveness of industries in the global market. The purpose of this paper is to present a line balancing methodology consisting of the combination of a heuristic model and an exact algorithm with intelligent task location or line zone constraints. The objective is to find a minimum cost solution in a feasible computational time with a realistic cost function considering short-term operation costs, task-related and workstation capital in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…This requires manufacturers to search for methods to minimize costs at all stages of production. To meet the challenges of balancing assembly lines with considering costs exact methods, heuristic and metaheuristic approaches can be applied [15][16][17].…”
Section: Methods and Models To Improve The Assembly Line Productionmentioning
confidence: 99%
“…This requires manufacturers to search for methods to minimize costs at all stages of production. To meet the challenges of balancing assembly lines with considering costs exact methods, heuristic and metaheuristic approaches can be applied [15][16][17].…”
Section: Methods and Models To Improve The Assembly Line Productionmentioning
confidence: 99%
“…Stiff competitive environment requires the industries using assembly lines to produce products at a very low cost without comprising on the quality of the product in a reasonable time. To remain competitive, the manufacturers need to speed up the time to market and at the same time to minimize the manufacturing cost [2]. Different set of tasks are to be executed in a set of predefined workstations in a time efficient manner in an assembly line.…”
Section: Introductionmentioning
confidence: 99%
“…Amen's study is used as the basis of the research work of Scholl and Becker [11] and it is shown in their work that one of the rules developed by Amen is incorrect and presented a corrected and simplified version of this rule. Padrón et al [2] presented a line balancing methodology which combines a heuristic model and exact algorithm with an objective of minimizing cost in a feasible computational time. Cost function considered includes short term operating costs, task and work station capital investment costs.…”
Section: Introductionmentioning
confidence: 99%
“…In product development, current global market con tinuously gives pressure to manufacturer to compete with competitors from all over the world. Manufacturer needs to speed up the time to market and at the same time minimise the manufacturing cost to ensure that their products remain competitive [1]. Assembly is considered one of the important processes in manufacturing.…”
Section: Introductionmentioning
confidence: 99%